2021
DOI: 10.3390/brainsci11070858
|View full text |Cite
|
Sign up to set email alerts
|

Music Stimulation for People with Disorders of Consciousness: A Scoping Review

Abstract: Music stimulation is considered to be a valuable form of intervention for people with severe brain injuries and prolonged disorders of consciousness (i.e., unresponsive wakefulness/vegetative state or minimally conscious state). This review was intended to provide an overall picture of work conducted during the last decade to assess the impact of music on behavioral and non-behavioral responses of people with disorders of consciousness. Following the PRISMA-ScR checklist, a scoping review was carried out to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…It was beyond the aim of this study to assess the specificity for preferred music of the observed cortical response. The main information that we would need to assess the level of consciousness of the patients would be cortical responsivity to any external stimuli; response to favorite music is among the most promising targets to evaluate responsiveness in patients with disorders of consciousness [ 44 ]. Further measurements should be performed intermodally with parallel electrophysiology by means of EEG, acoustic evoked potentials, and/or functional brain imaging with fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…It was beyond the aim of this study to assess the specificity for preferred music of the observed cortical response. The main information that we would need to assess the level of consciousness of the patients would be cortical responsivity to any external stimuli; response to favorite music is among the most promising targets to evaluate responsiveness in patients with disorders of consciousness [ 44 ]. Further measurements should be performed intermodally with parallel electrophysiology by means of EEG, acoustic evoked potentials, and/or functional brain imaging with fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, responsecontingent stimulation may involve the use of music, such as songs and instrumental pieces, voices of loved ones addressing the patients, as well as multimodal stimulation events (e.g., visual and auditory stimuli that may be delivered alternatively or in combination). Another general similarity between the response-contingent stimulation and the other strategies is that the type of stimulation presented to the patients is considered to be relevant/meaningful and pleasant for them [15,25,28,50,55].…”
Section: Similarities and Differences Between The Response-contingent...mentioning
confidence: 99%
“…The response-contingent stimulation strategy typically uses brief stimulation events (e.g., 10-or 15-s events) after each response occurrence. The other strategies generally rely on longer periods of stimulation delivery [15,55].…”
Section: Similarities and Differences Between The Response-contingent...mentioning
confidence: 99%
See 2 more Smart Citations